Insights into the structure–function relationship of missense mutations in the human TOP2A protein in ovarian cancer - Kavitha, Kannan; Mohanapriya, Arumugam (Frontiers in Physics, 2024)
Topoisomerase 2-alpha is a nuclear protein responsible for the maintenance of the topological state of DNA.TOP2A is highly upregulated in ovarian cancer and its copy number is an important prognosis factor. A large number of SNP, insertion, and deletion mutations have been reported in TOP2A.Thus, a structural and functional study of missense SNPs was carried out to screen potentially damaging mutations. The 193 nonsynonymous SNPs in the coding region of TOP2A in the dbSNP database were selected for in-silico analysis. The deleterious SNPs were screened using SIFT, Polyphen-2, SNAP2, and SNPs&Go and we got four possibly damaging SNPs at the end (Y481C, N7741, E922K, and R1514W).The mutants Y481C and E922K were predicted to be highly deleterious and showed decreased protein stability than native protein as predicted by I-Mutant 3.We used the Swiss model to model the structure of these two mutants and the structural attributes of modeled mutants were studied using HOPE Project, SPPIDER, SRide, and HBAT which predicted small variations from the native protein. Molecular dynamics simulation demonstrated a decrease in RMSD and radius of gyration of two mutants, relative to the native protein. Molecular docking of TOP2A with etoposide suggests that mutations may lead to resistance to TOP2A-targeted chemotherapy. In addition, relative expression analysis performed by qRT-PCR also reveals that there is a threefold increase in the expression levels of TOP2A protein in ovarian adenoma cancer cell lines. Our analysis reveals that Y481C and E922K are highly damaging variants of TOP2A, which alter the protein dynamics and may be implicated in causing ovarian cancer.